Changes in cause-specific mortality trends across occupations in working-age Japanese women from 1980 to 2015: a cross-sectional analysis - Bibha Dhungel; Kuniyasu Takagi; Shijan Acharya; Koji Wada; Stuart Gilmour (BMC, 2022)
Abstract Background Reducing health inequalities is an important public health challenge. Many studies have examined the widening health gap by occupational class among men, but few among women. We therefore estimated variation in absolute and relative mortality by occupational category across four leading causes of mortality-cancer, ischaemic heart disease, cerebrovascular disease, and suicide-to explore how occupational class is associated with health among working women aged 25-64 in Japan. Methods We conducted a repeated cross-sectional study using Poisson regression analysis on each five-yearly mortality data from 1980 to 2015, obtained from the National Vital Statistics and the Japanese Population Census. Results There was a decreasing trend in mortality from all cancers, ischaemic heart disease, cerebrovascular disease, and suicide among women in all occupational groups from 1980 to 2015. Agriculture workers had higher risk of mortality than professional workers for all four causes of death. The absolute difference in mortality rates for all cancers and cerebrovascular disease was higher in 2000-2015 than 1980-1995. The mortality trend among clerks and sales workers decreased after 2000, except for suicide. Conclusions Mortality rates from all four causes are higher among agriculture workers compared to professional workers, and attention is needed to reduce this mortality gap. Continuous monitoring of ongoing mortality trends is essential to ensure better health and wellbeing in Japan.